Maternal Infections, Antibiotics, Steroid Use, and Diabetes Mellitus Increase Risk of Early-Onset Sepsis in Preterm Neonates: A Nationwide Population-Based Study - Hao-Yuan Lee; Yu-Lung Hsu; Wen-Yuan Lee; Kuang-Hua Huang; Ming-Luen Tsai; Chyi-Liang Chen; Yu-Chia Chang; Hung-Chih Lin (Pathogens)
The global evolution of pathogens causing early-onset sepsis (EOS), a critical condition in preterm infants, necessitates a re-evaluation of risk factors to develop updated prevention and treatment strategies. This nationwide case–control study in Taiwan analyzed data from the National Health Insurance Research Database, Birth Reporting Database, and Maternal and Child Health Database from 2010 to 2019. The study included 176,681 mother–child pairs with preterm births. We identified 2942 clinical EOS cases from 5535 diagnosed sepsis cases, excluding unlikely cases. A control group of 14,710 preterm neonates without EOS was selected at a 1:5 ratio. Clinical EOS increased since 2017. Adjusted logistic regression identified significant EOS risk factors in preterm infants, including maternal fever, chorioamnionitis, maternal diabetes mellitus, maternal antibiotic usage, very preterm birth, birth weight (all with p < 0.001), maternal pneumonia (p = 0.002), and maternal CS (p = 0.004). Effective treatment of maternal conditions like diabetes, fever, and infections is essential to prevent EOS in preterm infants. Key measures include reducing unnecessary antibiotics or steroids, minimizing unnecessary cesarean sections, avoiding premature or prolonged rupture of membranes (PPROM), and increasing gestational age and neonatal birth weight. High-risk preterm neonates should be closely monitored for EOS and considered for antibiotics when warranted.